If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 8)(3x + -2) = 0 Reorder the terms: (8 + 2x)(3x + -2) = 0 Reorder the terms: (8 + 2x)(-2 + 3x) = 0 Multiply (8 + 2x) * (-2 + 3x) (8(-2 + 3x) + 2x * (-2 + 3x)) = 0 ((-2 * 8 + 3x * 8) + 2x * (-2 + 3x)) = 0 ((-16 + 24x) + 2x * (-2 + 3x)) = 0 (-16 + 24x + (-2 * 2x + 3x * 2x)) = 0 (-16 + 24x + (-4x + 6x2)) = 0 Combine like terms: 24x + -4x = 20x (-16 + 20x + 6x2) = 0 Solving -16 + 20x + 6x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(-8 + 10x + 3x2) = 0 Factor a trinomial. 2((-4 + -1x)(2 + -3x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-4 + -1x)' equal to zero and attempt to solve: Simplifying -4 + -1x = 0 Solving -4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 0 + 4 -1x = 0 + 4 Combine like terms: 0 + 4 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4Subproblem 2
Set the factor '(2 + -3x)' equal to zero and attempt to solve: Simplifying 2 + -3x = 0 Solving 2 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3x = 0 + -2 -3x = 0 + -2 Combine like terms: 0 + -2 = -2 -3x = -2 Divide each side by '-3'. x = 0.6666666667 Simplifying x = 0.6666666667Solution
x = {-4, 0.6666666667}
| m^2+15=8m | | 14m+n-6m+9n= | | 15-x(3)+2x=20 | | B=p+4a+3c | | x+x-2x+4x-1=4-x | | 7x+9(1-2x)=4-7(x-1) | | B=p+4a+33c | | 3b+2b-2=13 | | 3x-17+2x+1=25-x | | 3x-17+2x+1=25 | | 18+3(90-x)=90 | | x-49=8 | | s(t)=5t^2+15t | | (9x+4)-(-9x+8)= | | 77/11(5-3) | | 2[x+6]=2[-x+6.5] | | 4x+5=3x-14 | | x(4+3)=5-8x | | -4a=14a-12[4a+10] | | (x+7)(5)=45 | | -3[2u+5]+3.5u=-1u | | 100-50/5•10 | | f(7)=8x-3 | | 2b^2-9b-45=0 | | -7+8[5-3s]=3[7-9s] | | 4g+3[g-2]=-5[g-4]-g | | N/18=6/8 | | 0=×-9/x^2-81 | | 2b+4[b-6]=-2[2b-14]+98 | | 5x-7+x=3 | | 8x=540 | | 1/6[6w-12]=6-2[w-2] |